Da'wah Based on Socio Cultural Capital in the Prevention of Radicalism and Religious Conflict - Musthofa, Chabib; Prihananto, Prihananto (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
This study focuses on the growth and development of radicalism in the Lamongan Regency area and the forms and variants of co-religious conflicts in the Tuban Regency area. These two focuses do not intend to compare Lamongan and Tuban as study destinations but explore the two regions with different questions. The next focus is the da'wah model based on socio cultural capital in preventing radicalism and religious conflicts in Lamongan Regency and Tuban Regency. This research uses a qualitative approach with the type of grounded theory according to the stages of the type of research. Socio cultural capital is diverse and meaningful, stretching from the potential of natural resources, economy, culture, customs, arts, and religion. The results of the analysis show that the dominant factors that cause the growth of radical ideas in Lamongan Regency are limited religious knowledge and insight, mistakes in choosing teachers, low levels of economic welfare, provocation of online media, sectarianism, disappointment with social, political, economic and legal conditions, and weak government control over educational institutions and pesantren affiliated with radical groups. The form of religious conflict that occurred in Tuban Regency was a peaceful action, which is an action carried out by Muslims without violence in order to address sectarian and communal issues. The socio cultural capital of the Lamongan and Tuban communities has a diversity ranging from the potential of natural resources, economy, culture, customs, arts, and religion, giving birth to five da'wah models for preventing radicalism and religious conflicts. The five da'wah models in question are economic-based, institution-based, village-based mosques, pesantren, and based on local wisdom.